Variação genética, interação genótipo solo e ganhos na seleção em teste de progěnies de Corymbia citriodora Hook em Luiz Antonio, São Paulo - Morais, Euripedes; Zanatto, Antonio Carlos Scatena; Freitas, Miguel Luiz Menezes; De Moraes, Mário Luiz Teixeira [UNESP]; Sebbenn, Alexandre Magno (My University, 2010)
The aim of this study was to investigate the genetic variation, the genotype × soil interaction and the selection among and within Corymbia citriodora progenies in three different kinds of soils (Red Latossol, Quartz Sand and Purple Latossol), which occur in the Luiz Antônio Experimental Station, São Paulo State, Brazil. The progeny test was established 1983, using 56 open-pollinated families of C. citriodora. Twenty fve years after planting the following traits were measured: height, diameter at breast height (Dbh), stem form and survival. Best growth occurred in Purple Latossol. Significant differences among progenies were detected for most traits in all sites, suggesting the possibility of improvement by selection. In the analysis with sites, Significant differences among locals, progenies and genotypes × soil interaction were detected, confiming that the tested material has sufficient genetic variation to be explored by selection in all sites. The analysis of genotype × soil interaction indicates that growth traits present single interaction and the same progenies can be selected in each site. On the order hand, genotype × soil interaction for stem form and survival was complex; and specifc progenies need to be selected for each kind of soil. The population, due to its high genetic variation and strong genetic control of traits, permits to obtain considerable genetic gains by selection among and within progenies.
Genetic variation, genotype x soil interaction and genetic gains in a Corymbia citriodora Hook progeny test in Luiz Antonio, São Paulo, Brazil
Keywords: Eucalyptus; Progeny test; Soil; Tree breeding; Corymbia; Diameter-at-breast heights; Experimental stations; Genetic control; Genetic gain; Genetic variation; Growth traits; Open-pollinated families; Progeny tests; Quartz sand; Soil interaction; Stem form; Complexation; Forestry; Genes; Genetic engineering; Oxide minerals; Quartz; Soils